The influence of the role conflict and role ambiguity towards counseling competency in supervision among trainee counselors in Malaysia - Arifin, Suhaili; Mohd Noah, Sidek; Wan Jaafar, Wan Marzuki; Zakaria, Noor Syamilah (Human Resource Management Academic Research Society, 2019)
This study was a correlational research aiming to investigate the relationship between role conflict and role ambiguity, and counseling competencies among trainee counselors in the supervision process. Next, this study also seeks to examine the influence of both factors towards the study’s dependent variables. For the respondents, 217 trainee counselors and 67 supervisor lecturers from nine public universities in Malaysia were involved. Two instruments were used to measure the variables in this study namely The Role Conflict and Role Ambiguity Inventory (RCRAI) and Counseling Competencies Scale (CCS). RCRAI was administered to measure the role conflict and role ambiguity among trainee counselors, while CCS functions to assist the supervisors in evaluating the counselors’ competencies. Based on the study findings, there was a significant correlation between role conflict and role ambiguity with counseling competencies r =.170, p<.05; and r =-.542, p<.05, respectively. For the multiple regression analyses, it is reported that the model was a significant predictor of counseling competencies, R2= 2.95, F(2, 201) = 41.994, p< .000. The model also indicates that only role ambiguity had contributed significantly (?= -.434, p<.05), while role conflict had not (? =-.046, p>.05). All these findings provide future research directions to improve the level of competencies among the trainee counselor in the supervision process. For this purpose, the study implications on counselor competencies in the supervision as well as on the relationship between both the supervisor and trainee are discussed.